Economic evaluation of a novel community-based diabetes care model in rural Mexico: a cost and cost-effectiveness study. Issue 4 (7th April 2021) - Duan, Kevin I; Rodriguez Garza, Francisco; Flores, Hugo; Palazuelos, Daniel; Maza, Jimena; Martinez-Juarez, Luis Alberto; Elliott, Patrick F; Moreno Lázaro, Elena; Enriquez Rios, Natán; Nigenda, Gustavo; Palazuelos, Lindsay; McBain, Ryan K
Abstract : Objectives: Diabetes is the leading cause of disability-adjusted life years in Mexico, and cost-effective care models are needed to address the epidemic. We sought to evaluate the cost and cost-effectiveness of a novel community-based model of diabetes care in rural Mexico, compared with usual care. Design: We performed time-driven activity-based costing to estimate annualised costs associated with typical diabetes care in Chiapas, Mexico, as well as a novel diabetes care model known as Compañeros En Salud Programa de Enfermedades Crónicas (CESPEC). We conducted Markov chain analysis to estimate the cost-effectiveness of CESPEC compared with usual care from a societal perspective. We used patient outcomes from CESPEC in 2016, as well as secondary data from existing literature. Setting: Rural primary care clinics in Chiapas, Mexico. Participants: Adults with diabetes. Interventions: CESPEC is a novel, comprehensive, diabetes care model that integrates community health workers, provider education, supply chain management and active case finding. Outcome measure: The primary outcome was the incremental cost-effectiveness of CESPEC compared with care as usual, per quality-adjusted life year (QALY) gained, expressed in 2016 US dollars. Results: The economic cost of the CESPEC diabetes model was US$144 per patient per year, compared with US$125 for diabetes care as usual. However, CESPEC care was associated with 0.13 additional years of health-adjusted life expectancy compared with usual care and 0.02 additional years in the first 5 years of treatment. This translated to an incremental cost-effectiveness ratio (ICER) of US$2981 per QALY gained over a patient's lifetime and an ICER of US$10 444 over the first 5 years. Findings were robust to multiple sensitivity analyses. Conclusions: CESPEC is a cost-effective, community-based model of diabetes care for patients in rural Mexico. Given the high prevalence and significant morbidity associated with diabetes in Mexico and other countries in Central America, this model should be considered for broader scale up and evaluation.